Glucose stimulates chondrocyte differentiation of vascular smooth muscle cells and calcification: A possible role for IL‐1β. Issue 19 (12th August 2015) - Bessueille, Laurence; Fakhry, Maya; Hamade, Eva; Badran, Bassam; Magne, David
Abstract : Vascular calcification is a hallmark of type 2 diabetes. Glucose stimulates calcification in culture of vascular smooth muscle cells (VSMCs) but the underlying mechanisms remain obscure. We observed that high glucose levels stimulated mouse and human VSMC trans‐differentiation into chondrocytes, with increased levels of Sox9, type II collagen, glycosaminoglycan and Runx2 expression, and increased alkaline phosphatase activity and mineralization. These effects were associated with increased expression of IL‐1β, which stimulated alkaline phosphatase and calcification, suggesting that glucose induces chondrocyte differentiation of VSMCs, possibly through IL‐1β activation. Abstract : We explored the effects of high glucose concentration on mouse and human VSMCs. High glucose levels stimulate chondrocyte differentiation of VSMCs and calcification. IL‐1β levels raise in association with trans‐differentiation and calcification. IL‐1β mimics the effects of high glucose levels on calcification.